“Numa cidade de nome Natal, existe um povo chamado judeu” o proto-judaísmo da comunidade judaica potiguar a partir do estabelecimento entorno do Centro Israelita do Rio Grande do Norte – CIRN - Tavares, Diego Fontes de Souza (2022)
In the city of Natal of the 20th century, a new religious community was about to be born with the arrival of a Ukrainian family fleeing from the oppressions to their ethnicity. Escaping from the constant pogroms that decimated the Jewish population in Eastern Europe, the Palatnik family headed to the New World under the promises of work and land for cultivation granted to the Europeans as an economic policy in a post-slavery country, besides the desired religious freedom, so prized by these people. Established in Natal, and under the precepts of the Law to constitute a kehilla and to fulfill their religious rites, more Jews flocked to the city to the point of founding a Jewish community there, the Israelite Center of Rio Grande do Norte (CIRN). It is based on this Jewish presence in the capital of Rio Grande do Norte that the present thesis proposes a historical discussion about these Jews and their establishment in Natal, examining their religiosity as a guide for their behavioral conduct - regardless of the location and time in which they are - guided by the sacred books of the Torah, Tanakh, Talmud and Sidur, the main sources that guide this way of life. The thesis establishes an examination of these works to allude to their influence on Jewish life, problematizing them historically and theoretically, highlighting the anachronisms existing in the construction of these sacred books as national constitutions and exposing the intentionalities of the priestly body of the Josian reform (VII B.C.E.) in establishing and theologically structuring that ritual symbolic language. The research also exposes a documental survey about the CIRN members buried in the Israelite Cemetery, an important pillar of the Natal kehilla, and includes a historical discussion about the Jewish diaspora process that culminated in the settlement of Jews, New-Christians and Maroons in the Brazilian northeast of the 16th, 17th and 20th centuries. To this end, historical sources and the Deuteronomist theory were used, furthermore making use of theoreticians such as Mircea Eliade and his theory of the sacred, in an analysis of the Jewish ritual language as the theatricalization of the ancestral mythical narrative. As sources, public and private archives were consulted, as well as the memory of the Jews who reactivated the CIRN and of those who currently compose it, relying on reports of both conventional Jews and Anusim. In tracing these historical and theoretical discussions, the way of life for the Jew was established, finding that their ritual activities are mythical adaptations that have suffered and suffer resignifications over time. The thesis also designates that a cohesive and strong Potiguar Jewish community was consolidated, but it waned and had its activities terminated in 1968 due to the absence of Jews, since those who composed it at the time were migrating to other regions of the country. The CIRN was reactivated in 1979 by an expressive number of Jews who are no longer Ashkenazim, but by a group of people who declare themselves to be Jews through the Sephardic identity of their ancestors - and who are also resignifying the Jewish liturgy.